2010
DOI: 10.1021/cm100729d
|View full text |Cite
|
Sign up to set email alerts
|

High-κ Dielectric Sol−Gel Hybrid Materials Containing Barium Titanate Nanoparticles

Abstract: Novel high-κ thin composite films with excellent breakdown strength were synthesized using nonhydrolytic sol-gel processing. Organic-inorganic hybrid materials with high electronic polarizability were prepared as the matrix material to form a covalently bonded interface with the organically modified barium titanate (TBT) nanoparticles through a chemical cross-linking reaction. To enhance the dispersion stability of barium titanate (BT) nanoparticles in the matrix, the chemical nature of their surfaces was modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 34 publications
0
58
0
Order By: Relevance
“…Compared with the reported ceramic/PVDF composites and conductive metal Zn/PVDF [5,7,9,20,21], the dielectric constant of PVDF/V 2 O 5 composites is significantly higher at low filler content. Furthermore, it can be obviously found that our V 2 O 5 /PVDF composites possess higher dielectric constant than other semiconductor/polymers nanocomposites, such as ZnO/PVDF, TiO 2 /polystyrene, and ZnO/ polyethylene reported at a low filler content [10,22,23].…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Compared with the reported ceramic/PVDF composites and conductive metal Zn/PVDF [5,7,9,20,21], the dielectric constant of PVDF/V 2 O 5 composites is significantly higher at low filler content. Furthermore, it can be obviously found that our V 2 O 5 /PVDF composites possess higher dielectric constant than other semiconductor/polymers nanocomposites, such as ZnO/PVDF, TiO 2 /polystyrene, and ZnO/ polyethylene reported at a low filler content [10,22,23].…”
mentioning
confidence: 72%
“…Thus, it is a key issue to enhance dielectric permittivity of polymers while retaining other excellent performances. One versatile route is to disperse a high dielectric constant ceramic powder [5,6] into the polymer matrix [7][8][9], which can combine excellent dielectric behavior of fillers with superior processing property and chemical stability from the polymers. However, the excellent dielectric properties of such composites need high particle concentration (over 60 vol%), which can lead to the degradation of mechanical properties and processability of the polymers.…”
mentioning
confidence: 99%
“…6,7,14,15 Most previous studies on the size effect in BaTiO 3 were focused on nominally bare particles, polycrystalline ceramics or even BaTiO 3 /polymer composites. [19][20][21][22][23][24] For comparison, micron-sized BaTiO 3 powder was also prepared via the solid-state reaction approach by reacting stoichiometric amounts of TiO 2 (purity 99.99 wt.%) and BaCO 3 (purity 99.9 wt.%) at 1373 K for 6 h.…”
Section: Introductionmentioning
confidence: 99%
“…However, dielectric loss decreased at a low frequency range and then increased. The reason was that the space charge polarization contributed to the main part of the loss tangent while the conduction contributed less as the frequency increasing [33]. In addition, the maximum value of the dielectric loss was lower than 0.1 within the testing frequency range.…”
Section: Dielectric Properties Of Compositesmentioning
confidence: 96%
“…For instance, in chemical imidization, the dielectric constant was 7.745 when PVDF content was as high as 50 wt.%, which was about 1.5 times higher than that of composites synthesized by thermal imidization. The more uniform distribution of the composites synthesized by chemical imidization may be propitious to enhance the dielectric constant [33]. In addition, in thermal imidization method, the dielectric constant drastically increased to 5.7 when 30 wt.% PVDF was added, whereas when PVDF exceeded 30%, the dielectric constant decreased to 5.18.…”
Section: Dielectric Properties Of Compositesmentioning
confidence: 99%